Анализ динамических реакций при падении контейнера-упаковки с радиоактивными отходами - Бирюков, О. В.; Андреев, Юрий Михайлович; Лавинский, Денис Владимирович; Соболь, Владимир Николаевич (НТУ "ХПИ", 2007)
The method and results of the analysis of dynamic reactions, kinematics parameters and stress-strain state for the falling nuclear waste package are presented. The analysis of impact interaction by using the SAE of multibody system dynamics is done. The stress-state analysis of the package elements by finite element method (FEM) is given.
Keywords: атомные станции; ядерное топливо; транспортные упаковочные комплекты; кинематические параметры; упруго-диссипативное основание; ударные нагружения